Uterine leiomyoma in pediatric population: A case report and review of the literature - Martucci, Cristina; Crocoli, Alessandro; Persano, Giorgio; Marco, Bonito; Stracuzzi, Alessandra; Alaggio, Rita; Bertocchini, Arianna; Accinni, Antonella; Inserra, Alessandro (Frontiers in Pediatrics, 2022)
Uterine leiomyomas are rare in the pediatric population with less than 20 cases in adolescences reported in the literature. Furthermore, these masses represent a common presentation of gynecologic tumors with increasing age. We report a case of a 14-year-old female who presented with abdominal pain and increasing abdominal girth. Workup with ultrasound, CT and MRI demonstrated a large pelvic mass. Complete resection by median laparotomy was performed. The mass weighed 5596 g and was 29,5 x 27 x 19 cm; the pathological examination confirmed the hypothesis of leiomyoma. The patient remained asymptomatic at 3 months follow up.